(untitled) (Praxis Educativa, 2024)
An approach to the TPACK (Technological Pedagogical Content Knowledge) model with some of its variants is outlined. The review is oriented towards an alternative that places emphasis on its contextual aspects and teaching praxis. The model is a current theoretical reference for teacher training and affects both its development and the professional practice of teachers. This contribution arises from a doctoral thesis that addresses the emergence of digital technologies in professional teaching knowledge in the university environment. A collective case study is carried out, which is written and analyzed in narrative terms. A double methodological triangulation was applied, an initial one of survey instruments and another of perspectives for case validation. The narrative is assumed as a living expression of the framework of didactic, technological and disciplinary knowledge of the teaching staff, in a collective case situated and traversed by diverse trajectories, groupings and contexts.